A Rule based Fuzzy controlled Decision Support System for Intelligent Traffic Control System - Varshney, Monika; Srivastava, Azad Kumar; Aggarwal, Alok (International Journal of Computer Sciences and Engineering, 2025)
Congestion of roads particularly at different junction points due to vehicular traffic has become a chronic problem all around. Right now in India, a static timer is used to control the timing of the traffic light which results in a lot of problems. This paper introduces a fuzzy logic (FL) based decision support system (DSS) for intelligent traffic control system. The primary focus of the paper is on the algorithm used to reduce the time spent extra on the traffic light junction so as to save the fuel, time and to reduce the possibility of accidents occurring at the traffic light junction. The proposed system uses three input parameters; namely maximum length of vehicles behind traffic light, left green time, and no. of vehicles reaching the traffic light in a short period of time and one output, extension time which is used to control the congestion at the traffic light junction. Through decision support system, the meaning of transferred data is translated into linguistic variables that can be understood by non-experts. Mamdani inference engine is used to deduce from the input parameters